2015
DOI: 10.1186/s12939-015-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional survey on social, cultural and economic determinants of obesity in a low middle income setting

Abstract: IntroductionObesity is an increasing problem in South Asian countries and Sri Lanka is no exception. The socioeconomic determinants of obesity in Sri Lanka, and in neighbouring countries are inadequately described. Aim was to describe social, cultural and economic determinants of obesity in a representative sample from Kalutara District in Sri Lanka.MethodsThis was a cross sectional descriptive study conducted among adults aged 35–64 years. A representative sample was selected using stratified random cluster s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
5
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
(46 reference statements)
7
19
5
5
Order By: Relevance
“…Rathnayake et al [49] reported a higher average BMI for adult women than in our present study; conversely, the average BMI for women reported by Katulanda et al [8] (22.7 [4.5] kg/m 2 ) was lower than the current study. However, an average BMI for women similar to the present study has also been reported [45,47,48]. The mean BMI of women was higher than that of the men which is similar to previous studies [44,45,47].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Rathnayake et al [49] reported a higher average BMI for adult women than in our present study; conversely, the average BMI for women reported by Katulanda et al [8] (22.7 [4.5] kg/m 2 ) was lower than the current study. However, an average BMI for women similar to the present study has also been reported [45,47,48]. The mean BMI of women was higher than that of the men which is similar to previous studies [44,45,47].…”
Section: Discussionsupporting
confidence: 92%
“…However, an average BMI for women similar to the present study has also been reported [45,47,48]. The mean BMI of women was higher than that of the men which is similar to previous studies [44,45,47]. The mean WC of women (85.96 [9.53] cm) was higher than the Asian cut-off and previously reported values by Katulanda et al (76.8 [12.2] [49].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…while Indian study found that of abdominal obesity was 46.6% (women: 56.2%> men: 35.1%,) [14] study done Sri lank found that prevalence of overweight, obesity and abdominal obesity (high WC) were 33.2% (male 27.3%/female 38.7%), 14.3% (male 9.2%/female 19.2%) and 33.6% (male 17.7%/female 49.0%) respectively. [15] which is similar to our finding to some extent. our study differ from a study done Spain where all the values of obesity and abdominal obesity is less (16.6% in males and 15.2% in females ) [16] also Iran study had less prevalence of obesity (34.8%)and less abdominal obesity (28.3) but it is similar to our study in that female had higher prevalence of abdominal obesity than males [17] Netherlands study showed very low prevalence of obesity in compared to our study, it was 4 and 6% in men and women, respectively [18] …”
Section: Discussionsupporting
confidence: 82%
“…13 This was also consistent with the previous report that a higher prevalence of obesity was observed in the more educated, urban, high income and high social status segments of society. [14][15][16][17] Recently, in Drewnowski A's study, census tract level home values and college education were more strongly associated with obesity than household incomes. For each additional $100 000 in median home values, the census tract obesity prevalence was 2.3% lower.…”
Section: Discussionmentioning
confidence: 99%